2013
DOI: 10.1371/journal.pone.0053666
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptional Regulation of meis1 by Gfi1b and Its Co-Factors LSD1 and CoREST

Abstract: Gfi1b (growth factor independence 1b) is a zinc finger transcription factor essential for development of the erythroid and megakaryocytic lineages. To elucidate the mechanism underlying Gfi1b function, potential downstream transcriptional targets were identified by chromatin immunoprecipitation and expression profiling approaches. The combination of these approaches revealed the oncogene meis1, which encodes a homeobox protein, as a direct and prominent target of Gfi1b. Examination of the meis1 promoter sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 46 publications
(108 reference statements)
7
40
0
Order By: Relevance
“…MEL cells were cultured and differentiated as described previously (8,31 Mononucleosome Preparation and Demethylation Assays. Mononucleosomes were prepared as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEL cells were cultured and differentiated as described previously (8,31 Mononucleosome Preparation and Demethylation Assays. Mononucleosomes were prepared as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal anti-mouse rabbit serum was produced against the C-terminal 17 amino acids of Rcor3, affinity-purified, and used for Western blot analyses and ChIP. ChIP primers used were as described previously (8,31) and listed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of Rgs18 promoter sequences obtained from the mouse promoter arrays of these ChIP-on-chip screens (Chowdhury et al, 2013;Saleque et al, 2007) revealed the presence of quasi-consensus (AAATCT) and consensus (AAATCA) Gfi1-and Gfi1b-binding sites (Tong et al, 1998) in the 5′ untranslated region (UTR) and proximal protein coding regions of Rgs18, respectively (Fig. S1).…”
Section: Lineage-specific Regulation Of Rgs18 By Gfi1b and Lsd1mentioning
confidence: 99%
“…ChIP experiments were performed in MEL and L8057 cells as previously described (Chowdhury et al, 2013;Saleque et al, 2007) with anti-Gfi1b (Sc8559, Santa Cruz Biotechnology) and anti-LSD1 (ab17721, Abcam) antibodies. Primers used for qPCR amplification of ChIP DNA were: Rgs18 promoter (upstream), 5′-TCATTTCCTTCAACAATTCAGTAC-A-3′ and 5′-CGAATCTTTCCTCAGATTTTTCTTA-3′; Rgs18 promoter (downstream), 5′-ATGTGTGAATCAAAAGAGAAAACTTT-3′ and 5′-CACAGATATTCATCAATCATGCTACTT-3′; and Sµ, 5′-CTTGA-GCCAAAATGAAGTAGACTGT-3′ and 5′-ACAGTCCAGTGTAGG-CAGTAGAGTT-3′.…”
Section: Chipmentioning
confidence: 99%
“…GFI1B and its cofactors lysine (K)-specific demethylase 1A (LSD1, encoded by the Kdm1A gene) and rest corepressor 1 (RCOR1) have been identified in ChIP-Seq studies as key regulators of Meis1 [189]. The evidence that GFI1B plays a role in MK maturation has been recently further exemplified with the identification of a mutation creating a dominant-negative form of GFI1B leading to an autosomal dominant form of gray platelet syndrome [190].…”
Section: Meis1 and Its Regulator Gfi1bmentioning
confidence: 99%